Pelatihan Peningkatan Kompetensi Literasi dan Kualitas Pembelajarann Guru SD melalui Pendekatan Design Thinking di Kabupaten Muaro Jambi - Gati Ningsih, Arum; Rustam, Rustam; Priyanto, Priyanto; Akbar, Oky; Oktri Wini, Lusi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Type abstract in English here. In 2021, the government will replace the National Examination with the National Assessment (AN). National Assessment is a form of evaluation of the education system at the primary and secondary education levels. The assessment aims to measure cognitive, non-cognitive learning outcomes and the quality of the learning environment. Cognitive learning outcomes include reading literacy and numeracy. Cognitive learning outcomes are measured through the Minimum Competency Assessment (AKM). Based on the results of Public Education Report Card data, especially in the Jambi Province area, the data shows that learning outcomes are not yet optimal. Literacy and numeracy skills are still below minimum competency. This means that less than 50% of students have achieved minimum competency. Creativity is needed in learning to create a conducive learning atmosphere. By increasing the literacy competency and quality of learning of Muaro Jambi district elementary school teachers through reading informational texts and literary texts using a design thinking approach, it is hoped that they will provide understanding, strengthening and actualization with measurable control in order to achieve quality education. The implementation of this community service activity uses three methods, namely the lecture method, practice discussion and demonstration method. Data analysis is carried out by drawing conclusions through categorization, synthesis, interpretation and evaluation Whika produces descriptive meaning. The result of this activity is that elementary school teachers are able to compose informational text questions and simple literary texts that can be implemented in class.